Review of mobile learning: Languages, literacies, and cultures - Burston, Jack (My University, 2015)
While the targeted audience of Mark Pegrum’s Mobile Learning: Languages, Literacies and Cultures is not made explicit, its content is best suited to those endeavoring to understand MALL (Mobile-Assisted Language Learning) within the broader context of mobile learning. In this regard it is much more contemporary than historical, with nearly two thirds of its references dating from the past six years (2008–2013). The work is commendable for the background it provides on mobile learning across a wide instructional spectrum. Of particular note is the attention paid to initiatives in developing countries endeavoring to exploit mobile technologies to remedy high native-language illiteracy rates and overcome the educational disadvantages of women, especially in rural communities. This information is all the more valuable in that it derives mostly from international project reports, which is otherwise largely absent and unobtainable from published academic research sources. What the work gains in breadth in regard to mobile learning in general, however, it loses in depth in respect to MALL in particular. Of the book’s seven chapters, the first three are entirely devoted to general issues concerning mobile learning. In fact, only the fourth and fifth chapters focus explicitly upon language teaching. The sixth chapter concerns literacy in its broadest possible interpretation, of which reading and writing are but two of eight abilities discussed. Lastly, while taking most of its examples from language-based projects, the focus of the final chapter of the book is very much on the general issue of teacher and student training needed in the digital age.
Keywords: Languages; Mobile-Assisted Language Learning